Phonetic and ortographic interferences in the Romanian language spoken in Spain - Jieanu, Ioana (Vestnik za tuje jezike, 2012)
The article Phonetic and orthographic interferences in the Romanian language spoken in Spain presents some results of Romanian-Spanish contacts, from a double perspective: phonetically and orthographically. The purpose of the phonetic and orthographic influence of Spanish over the Romanian research entails the identification of linguistic consequences which the massive migration of Romanian people to Spain had. Analyzing the Romanian language of migration within Romanian communities from Spain, we have remarked two ways ofphonetic adaptation: the adaptation of Spanish borrowings to the Romanian phonetic system and the adaptation of the Romanian words to the Spanish phonetic system. Studying in parallel some audio texts recorded by 11 Romanian students in Spain, Castellón de la Plana, and some written texts from a forum, we concluded that borrowed words from Spanish are only phonetically adapted to the Romanian language, graphically speaking remaining unadapted.
Keywords: romunščina; Spanish; španščina; jezikovne interference; jeziki v stiku; prevzete besede; izposojenke; fonetika; phonetics; pravopis; orthography